3D Printing of Superhydrophobic Objects with Bulk Nanostructure. Issue 45 (28th September 2021) - Dong, Zheqin; Vuckovac, Maja; Cui, Wenjuan; Zhou, Quan; Ras, Robin H. A.; Levkin, Pavel A.
Abstract: The rapid development of 3D printing (or additive manufacturing) technologies demands new materials with novel properties and functionalities. Superhydrophobic materials, owing to their ultralow water adhesion, self‐cleaning, anti‐biofouling, or superoleophilic properties are useful for myriad applications involving liquids. However, the majority of the methods for making superhydrophobic surfaces have been based on surface functionalization and coatings, which are challenging to apply to 3D objects. Additionally, these coatings are vulnerable to abrasion due to low mechanical stability and limited thickness. Here, a new materials concept and methodology for 3D printing of superhydrophobic macroscopic objects with bulk nanostructure and almost unlimited geometrical freedom is presented. The method is based on a specific ink composed of hydrophobic (meth)acrylate monomers and porogen solvents, which undergoes phase separation upon photopolymerization to generate inherently nanoporous and superhydrophobic structures. Using a desktop Digital Light Processing printer, superhydrophobic 3D objects with complex shapes are demonstrated, with ultralow and uniform water adhesion measured with scanning droplet adhesion microscopy. It is shown that the 3D‐printed objects, owing to their nanoporous structure throughout the entire volume, preserve their superhydrophobicity upon wear damage. Finally, a superhydrophobic 3D‐printed gas‐permeable and water‐repellent microfluidic device and a hierarchically structured 3D‐printed super‐oil‐absorbent are demonstrated. Abstract : The principle of polymerization‐induced phase separation is exploited to 3D print superhydrophobic objects with bulk nanostructure and unlimited geometrical freedom. The bulk nanoporous structure of the 3D‐printed superhydrophobic objects not only makes them tolerant to abrasion damage, but also opens new possibilities in applications including gas‐permeable and water‐repellent microfluidics, as well as hierarchically structured super oil absorbents.